Rescue of cardiac leptin receptors indb/dbmice prevents myocardial triglyceride accumulation - Michael E. Hall; Matthew Maready; John E. Hall; David E. Stec (2014)
Increased leptin levels have been suggested to contribute to cardiac hypertrophy and attenuate cardiac lipid accumulation in obesity, although it has been difficult to separate leptin's direct effects from those caused by changes in body weight and adiposity. To determine whether leptin attenuates cardiac lipid accumulation in obesity or directly causes left ventricular hypertrophy (LVH), we generated a novel mouse model in which the long form of the leptin receptor (LepR) was “rescued” only in cardiomyocytes of obese db/db mice. Reexpression of cardiomyocyte leptin receptors in db/db mice did not cause LVH but reduced cardiac triglycerides and improved cardiac function. Compared with lean wild-type (WT) or db/db-cardiac LepR rescue mice, db/db mice exhibited significantly lower E/A ratio, a measurement of early to late diastolic filling, which averaged 1.5 ± 0.07 in db/db vs. 1.9 ± 0.08 and 1.8 ± 0.11 in WT and db/db-cardiac LepR rescue mice, respectively. No differences in systolic function were observed. Although db/db and db/db-cardiac LepR rescue mice exhibited similar increases in plasma triglycerides, insulin, glucose, and body weight, cardiac triglycerides were significantly higher in db/db compared with WT and db/db cardiac LepR rescue mice, averaging 13.4 ± 4.2 vs. 3.8 ± 1.6 vs. 3.8 ± 0.7 mg/g, respectively. These results demonstrate that despite significant obesity and increases in plasma glucose and triglycerides, db/db cardiac LepR rescue mice are protected against myocardial lipid accumulation. However, we found no evidence that leptin directly causes LVH.